CHARACTER ALTERATION OF CRUELLA FROM 101 DALMATIANS (1961) INTO CRUELLA MOVIE (2021) - Azzahra, Arynaa; Yuniar, Ata; Kusumastuti, Febiana; Calista Sumbayak, Sastila (CrossOver Journal of Adaptation Studies, 2023)
This journal researched Postmodernism from 101 Dalmatian movies and Cruella movies. The researchers are interested in evaluating the differences between 101 Dalmatians, produced in 1961, and Cruella, directed in 2021. The popularity of character transformation and the diverse eras introduced by these two films is the cause why these movies must be studied. The study’s goal was to examine Cruella’s transformation in both films. The researchers used the descriptive comparative approach to perform the research. The note-taking approach was employed in conjunction with Linda Hutcheon’s postmodernism theory. The researchers found that the differences lay in historical representation, including their nature, relationship, and goal in the movies.